GP.4 The epilepsy surgery experience in children with infantile spasms at a tertiary care centre in Canada. (June 2022) - Gettings, J; Shafi, S; Boyd, J; Snead, O; Rutka, J; Drake, J; McCoy, B; Jain, P; Whitney, R; Go, C
Abstract : Background: Infantile spasms (IS) is an epileptic encephalopathy, characterized by spasms, hypsarrhythmia, and developmental regression. This is a retrospective case series of children with IS who underwent epilepsy surgery at The Hospital for Sick Children (HSC) in Toronto, Canada. Methods: The records of 223 patients seen in the IS clinic were reviewed. Results: Nineteen patients met inclusion criteria. The etiology of IS was encephalomalacia in six patients (32%), malformations of cortical development in 11 patients (58%), atypical hypoglycaemic injury in one patient (5%), and partial hemimegalencephaly in one patient (5%). Nine patients (47%) underwent hemispherectomy and 10 patients (53%) underwent lobectomy/lesionectomy. Three patients (16%) underwent a second epilepsy surgery. Fifteen patients (79%) were considered ILAE Seizure Outcome Class 1 (completely seizure free; no auras). The percentage of patients who were ILAE Class 1 at most recent follow-up decreased with increasing duration of epilepsy prior to surgery. Developmental outcome was improved in 14/19 (74%) and stable in 5/19 (26%) patients. Conclusions: Our study found excellent seizure freedom rates and improved developmental outcomes following epilepsy surgery in patients with a history of IS with a structural lesion detected on MRI brain.